The Role And Competence Of Sharia Auditors In Supporting The Performance Of Sharia Banking - Umi Suswati Risnaeni; Amalus Sholeha (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
This article aims to provide an overview of the role of shariah halal auditors in the guarantee system in sharia banking in Indonesia. Sharia banking is a financial institution that must be examined and tested with smart products, and it is operated by an independent institution which is a